2017
DOI: 10.12659/msm.902197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Prognostic Implications of Quantifying Pulmonary Contusion Volume in Patients with Blunt Chest Trauma

Abstract: BackgroundPulmonary contusion (PC) is the most frequent blunt chest injury which could be used to identify patients at high-risk of clinical deterioration. We aimed to investigate the clinical correlation between PC volume and outcome in patients with blunt chest trauma (BCT).Material/MethodsBCT patients with PC were identified retrospectively from the prospectively collected trauma registry database over a 2-year period. Contusion volume was measured and expressed as percentage of total lung (CTCV) volume usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
3
17
0
13
Order By: Relevance
“…Lung contusion was found in 71.4% of children with chest injury and in 66.7% of adult. This is in accordance with Mahmood et al (7) who stated that pulmonary contusion is the most frequent chest injury (25-80%) and Skinner et al (4) stated that children suffer more lung contusions.…”
Section: Discussionsupporting
confidence: 90%
“…Lung contusion was found in 71.4% of children with chest injury and in 66.7% of adult. This is in accordance with Mahmood et al (7) who stated that pulmonary contusion is the most frequent chest injury (25-80%) and Skinner et al (4) stated that children suffer more lung contusions.…”
Section: Discussionsupporting
confidence: 90%
“…Several institutional studies have shown that contused lung volumes positively correlate with degree of impaired oxygenation, risk of developing ARDS, and prolonged intubation. 7,8,14 Validating these studies may inform clinical decision-making, such as identifying a cutoff of contused lung volume that significantly increases risk of respiratory failure and perhaps pre-emptively admitting these patients to the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mahmood et al reported that 20% contused lung volumes were associated with increased risk of acute respiratory distress syndrome and prolonged mechanical ventilation among patients who suffered blunt chest trauma. 7 Validating clinically meaningful contused lung volume cutoffs requires further individual CT scan evaluations at the institutional level. Future studies exploring the association between contused lung volumes and outcomes should also note that pulmonary contusions are not static injuries; evolution of traumatic pulmonary contusions requires better characterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe thoracic deformities can affect cardiopulmonary function, reduce chest and lung compliance, and lead to impaired respiratory function. These mechanical and inflammatory sequelae often complicate the care of patients with CBT and increase the risk of pneumonia, acute respiratory failure, and even acute respiratory distress syndrome (ARDS) [11]. Patients with chest trauma and rib fractures often show respiratory dysfunction, especially when a flail chest is present.…”
Section: Discussionmentioning
confidence: 99%